Evolvability in the fossil record. Issue 2 (May 2022) - Love, Alan C.; Grabowski, Mark; Houle, David; Liow, Lee Hsiang; Porto, Arthur; Tsuboi, Masahito; Voje, Kjetil L.; Hunt, Gene
Abstract: The concept of evolvability—the capacity of a population to produce and maintain evolutionarily relevant variation—has become increasingly prominent in evolutionary biology. Paleontology has a long history of investigating questions of evolvability, but paleontological thinking has tended to neglect recent discussions, because many tools used in the current evolvability literature are challenging to apply to the fossil record. The fundamental difficulty is how to disentangle whether the causes of evolutionary patterns arise from variational properties of traits or lineages rather than being due to selection and ecological success. Despite these obstacles, the fossil record offers unique and growing sources of data that capture evolutionary patterns of sustained duration and significance otherwise inaccessible to evolutionary biologists. Additionally, there exist a variety of strategic possibilities for combining prominent neontological approaches to evolvability with those from paleontology. We illustrate three of these possibilities with quantitative genetics, evolutionary developmental biology, and phylogenetic models of macroevolution. In conclusion, we provide a methodological schema that focuses on the conceptualization, measurement, and testing of hypotheses to motivate and provide guidance for future empirical and theoretical studies of evolvability in the fossil record.